The Case for Energy-Proportional Computing. - Barroso, Luiz André; Hölzle, Urs (Computer (00189162), 2007)
The article focuses on energy efficiency and computing. Saving energy is a huge issue for servers and data center operations, with a particular focus on reducing energy costs. Laptop computers only require high energy efficiency during usage, but during sleep or standby mode they consume little to no energy. Included is a chart that shows the central processing unit (CPU) utilization of more than 5,000 servers during a six-month period. Spreading data across several CPU improves data availability because if a crash occurs it is less likely that data will be lost. Topics include energy efficiency at varying power levels, and the push for more energy-efficient computers.